Soft Power & Hegemony: Gramsci, Nye, and Cox’s Perspectives - Febriani, Rika; Hamdi, Irwan (Jurnal Filsafat "WISDOM", 2024)
This article highlights the significance of soft power and hegemony in the realms of international relations theory and political philosophy. Soft power serves as a political strategy utilized by nations to attract and shape ideas in other countries through influence and persuasion. Similarly, Antonio Gramsci's concept of hegemony emphasizes the influence of societal ideas by employing moral and intellectual leadership through consensus. In enriching this analysis, it incorporates perspectives from Robert Cox, who deepen the understanding of how hegemony intertwines with global power structures, social forces, and the construction of world order. This article provides a theoretical review of Joseph S. Nye's soft power concept and Antonio Gramsci's notion of hegemony, comparing both at the epistemological level of political science, encompassing concepts, praxis, and values. The study is based on Nye's Soft Power (2004) and Gramsci's Selections from the Prison Notebooks (2007) through a literature review. This article concludes that these concepts share similarities, such as utilizing intellectual leadership, promoting awareness within the intellectual class, and targeting civil society as a crucial influencer.